2020
DOI: 10.1101/2020.02.05.936120
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

mRNA stem-loops can pause the ribosome by hindering A-site tRNA binding

Abstract: Although the elongating ribosome is an efficient helicase, certain mRNA stem-loop structures are known to impede ribosome movement along mRNA and stimulate programmed ribosome frameshifting via mechanisms that are not well understood. Using biochemical and single-molecule Förster resonance energy transfer (smFRET) experiments, we studied how frameshift-inducing stem-loops from E. coli dnaX mRNA and the gag-pol transcript of Human Immunodeficiency Virus (HIV) perturb translation elongation. We find that upon en… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(28 citation statements)
references
References 79 publications
2
26
0
Order By: Relevance
“…Rotation of the head relative to the body (also known as "head swivel") can achieve~20°. The opening between these 30S domains allows mRNA to sample conformations outside the mRNA tunnel 34,35 . ArfB dimerization likely shifts the mRNA dynamic equilibrium by fixing longer mRNAs outside the mRNA tunnel.…”
Section: -5; Supplementarymentioning
confidence: 99%
See 1 more Smart Citation
“…Rotation of the head relative to the body (also known as "head swivel") can achieve~20°. The opening between these 30S domains allows mRNA to sample conformations outside the mRNA tunnel 34,35 . ArfB dimerization likely shifts the mRNA dynamic equilibrium by fixing longer mRNAs outside the mRNA tunnel.…”
Section: -5; Supplementarymentioning
confidence: 99%
“…This indicates that mRNA downstream the P-site codon is conformationally unstable in the absence of a stabilizing A-site interaction. Furthermore, downstream mRNA with high propensity for secondary-structure formation can depart from the mRNA tunnel and fold in the A site 34,40 . It is possible therefore, that in addition to the truncated and rare-codon substrates, ArfB also recognizes no-go complexes with structured mRNA downstream the tunnel.…”
Section: -5; Supplementarymentioning
confidence: 99%
“…6). Similar fold changes upon induction while retaining the use of the T7 RNAP and promoter could be achieved by using a bicistronic design and adding stop codons and stem loops 23 before the IRES modules (Extended Data Fig. 7a).…”
Section: Resultsmentioning
confidence: 93%
“…Therefore, we decided to explore methods of reducing translational activity in the presence of canonical 5′ capping. By adding stop codons and stem loops 23 after a gene controlled by a constitutive promoter, we were able to reduce the basal expression of downstream mRNA despite the reliance on RNA polymerase II (Fig. 2c,d).…”
Section: Resultsmentioning
confidence: 97%
“…The slippery sequence allows cognate or near-cognate pairing of the P-site and A-site tRNAs in both 0 and −1 frames and thus makes frameshift thermodynamically favorable 26 . A number of previous studies demonstrated that when the slippery sequence is bound in the P and A sites of the ribosome and the FSS is positioned at the entry to mRNA tunnel of the small subunit, the rate of tRNA/mRNA translocation decreases by approximately an order of magnitude 11,[27][28][29][30][31] . We also recently demonstrated that, when positioned 11-12 nucleotides downstream of the P-site codon, FSSs can transiently escape the ribosome helicase and inhibit A-site tRNA binding by docking into the A site of the small (30S) ribosomal subunit 31 .…”
mentioning
confidence: 99%